CORPORATE SOCIAL RESPONSIBILITY STRATEGY IN THE HOSPITALITY INDUSTRY: A CASE STUDY OF GAIA COSMO HOTEL - Asriyani, Nabila; Fadillah, Dani (Universitas Muhammadiyah Jakarta, 2024)
This study aims to analyze Corporate Social Responsibility (CSR) strategies in the hospitality industry, with a case study on GAIA Cosmo Hotel. CSR is an important concept in modern business, involving corporate responsibilities towards the environment and surrounding communities. GAIA Cosmo Hotel, as part of the rapidly growing hospitality industry, implements various CSR strategies to enhance corporate reputation and deliver positive impacts on the environment and local communities. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with hotel management and analysis of company documents. The study seeks to gain a deeper understanding of the motivations for CSR, CSR practices, and the impact of CSR practices implemented by GAIA Cosmo Hotel. Several key findings emerged from this research. First, the primary motivation for GAIA Cosmo Hotel in implementing CSR is to maintain good relations with the local community and facilitate business operations. Second, the hotel’s CSR practices are divided into two categories: thematic CSR practices and regular CSR practices. Third, the implementation of CSR at GAIA Cosmo Hotel has a positive impact on the relationship between the company and the community. This research is expected to provide insights for other hospitality companies in designing and implementing holistic and sustainable CSR programs.